Examining Racial Bias in Education: A New Approach. (December 2016) - Warikoo, Natasha; Sinclair, Stacey; Fei, Jessica; Jacoby-Senghor, Drew
In this article we argue that social-psychological research on implicit racial associations—relatively unconscious associations based on race—is a fruitful area to explore for a greater understanding of how racial bias affects children in schools. We highlight the key insights of research on implicit racial associations and their implications for education. Further, we identify areas for research on implicit racial associations in education, calling for collaboration between scholars of racial inequality in education and scholars of implicit racial associations. This research is likely to provide a productive new perspective for understanding why and when teachers and other school personnel engage in behaviors that reproduce racial inequality, often in spite of best intentions and commitments to racial equity.